Design and financial parametric assessment and optimization of a novel solar-driven freshwater and hydrogen cogeneration system with thermal energy storage. (June 2021) - Delpisheh, Mostafa; Abdollahi Haghghi, Maghsoud; Mehrpooya, Mehdi; Chitsaz, Ata; Athari, Hassan
Abstract: The simultaneous production of electricity (semi-finished product), freshwater, and hydrogen uprooted from seawater has been proposed in this study through a brainchild setup based on solar energy and scrutinized from exergy and exergoeconomic perspectives. The solar subsystem consists of parabolic trough solar collectors in arrangement with thermal storage tanks capable of driving other subsystems in three different solar radiation modes (low, high, and no radiation) in the course of a day. An organic Rankine cycle is utilized to generate electricity which is consumed in a low-temperature electrolyzer to produce hydrogen. Furthermore, the cycle's heat loss is employed to produce freshwater via a desalination unit, part of which is used as the electrolyzer feed and the rest for other purposes. The parametric study and multi-criteria optimization are conducted. It is concluded that the system's cost per unit exergy increases by increasing current density and reduces by decreasing electrolyzer temperature and desalination top temperature. In the multi-criteria optimization case, the exergy efficiency of the system is acquired for the above-mentioned modes as 5.39%, 2.52%, and 3.61%, respectively. Moreover, the cost per unit exergy of these modes is found to be 80 $/GJ, 60.3 $/GJ, and 81.4 $/GJ, individually.